Franchising as a strategy for firm competitiveness: a case study of Dairiboard Zimbabwe Private Limited. - Chibondo, Rudo (Midlands State University, 2017)
This research was undertaken to evaluate the effectiveness of franchising as a strategy for Dairibord to achieve competitiveness. The research was motivated by the challenges that the company is facing such as stiff competition, decrease in sales volume and market share and high operational cost. The major aims of this research were to determine the contribution of franchising on sales volume and market share, determine the contribution of product distribution and trademark franchising in enhancing product availability and market coverage, establish the cost and benefits of business format franchising and determining other distribution forms that Dairibord can incorporate to improve company performance. Company sales and financial reports and published books, articles and journals were used for literature review to evaluate the opinions, concepts and arguments of various authors who previously researched on the similar concept under study. The researcher used descriptive and exploratory research designs and both questionnaires and interviews were used to collect data. The target population was 100 respondents and a sample size of 80 respondents was used. Pie charts, bar graphs, tables and continuous paragraphs were used to present and analyze data. The major findings and conclusions were that franchising is a distribution strategy that is enhancing product availability and market coverage for Dairibord. Franchising as a distribution channel increases sales volume and market share of the firm. Dairibord advertising campaigns, selling proven products and using a reputable brand name are some of the benefits a franchisee enjoys from franchising strategy. The franchisees incur high costs such as legal, labour, outlet set up and equipment purchasing cost and face challenges such as limited freedom, limited product line, and franchisor’s bad publicity. Loss of control, trademark infringement and misuse and loss of confidentiality are some of the challenges Dairibord face by implementing the franchising strategy. The researcher recommends Dairibord to venture into strategic alliances and joint venture so as to make use of other business’s resources to achieve its objective. Dairibord should increase the number of countries in which they do foreign direct investments so as to improve its performance. Dairibord should take the franchising distribution strategy to global markets hence introducing international franchising which enables the firm’s growth.